Let's first get the coefficients of the numerator: x^4 - 2x^3 + x + 3 = 1, -2, 0, 1, 3
<em>There is no x^2 in the expression, thus, the coefficient for x^2 = 0</em>
Zero of the denominator: x + 3; x = -3
Using synthetic division,
-3 I 1 -2 0 1 3
I_________________
-3 I 1 -2 0 1 3
I_________________
1
-3 I 1 -2 0 1 3
I_____-3___________
1 -5
-3 I 1 -2 0 1 3
I_____-3__15_______
1 -5 15
-3 I 1 -2 0 1 3
I_____-3__15_-45____
1 -5 15 -44
-3 I 1 -2 0 1 3
I_____-3__15_-45____
1 -5 15 -44
-3 I 1 -2 0 1 3
I_____-3__15_-45_132__
1 -5 15 -44 135
The remainder is 135. Which transforms it into 135/x+3.
Thus, the quotient of x^4 - 2x^3 + x + 3 divided by x + 3 is:
To convert 8% to decimal divide by 100
<span>8 ÷ 100 = 0.08</span>
Can you provide a picture?
I will come back to this when I am older
Answer:
1/2
Step-by-step explanation:
Given:
sinx=-1/2
cosy=√3/2
finding x
x=sin^-1(-1/2)
x=-π/6
x=-30°
finding y
cosy=√3/2
y=cos^-1(√3/2)
y=π/6
y=30°
Now finding cos(x-y)
cos(-π/6-π/6)
=cos(-π/3)
=1/2!